THE RELATIONSHIP BETWEEN STUDENTS’ MOTIVATION AND THEIR LEARNING ACHIEVEMENT - Hilva Yanuarti; Dian Rosmayanti (PROJECT (Professional Journal of English Education), 2018)
Among the factor influencing students learning, motivation becomes one of the momentous factors that  may affect students learning achievement. The aim of this study is to investigate the relationship between students’ motivation and their learning achievement. The subject were 88 second year students at Science major class of an Islamic high school in Cimahi City in the second semester of the Academic year 2018. The research uses quantitative corelation as a method consisting of two variables, namely students motivation (independent) and students achievement (dependent). The writers uses questionnaire as an instrument to collect the data and the student English score from their English teacher. The data analyze use SPSS. Finding from this study indicate that there are any relationship between students motivation and their learning achievement. The relationship between students’ motivation and their English learning achievement was   significantly and has Medium Correlation. When the result showing 0.580 appropriate with Pearson Correlation degree Value 0.41 s/d 0.60 = Medium Correlation. Keywords:  Relationship, Motivation, Achievement